Dosimetric comparison to the heart and cardiac substructure in a large cohort of esophageal cancer patients treated with proton beam therapy or Intensity-modulated radiation therapy. Issue 1 (October 2017) - Shiraishi, Yutaka; Xu, Cai; Yang, Jinzhong; Komaki, Ritsuko; Lin, Steven H.
Abstract: Purpose: To compare heart and cardiac substructure radiation exposure using intensity-modulated radiotherapy (IMRT) vs. proton beam therapy (PBT) for patients with mid- to distal esophageal cancer who received chemoradiation therapy. Methods and materials: We identified 727 esophageal cancer patients who received IMRT ( n = 477) or PBT ( n = 250) from March 2004 to December 2015. All patients were treated to 50.4 Gy with IMRT or to 50.4 cobalt Gray equivalents with PBT. IMRT and PBT dose–volume histograms (DVHs) of the whole heart, atria, ventricles, and four coronary arteries were compared. For PBT patients, passive scattering proton therapy (PSPT; n = 237) and intensity-modulated proton therapy (IMPT; n = 13) DVHs were compared. Results: Compared with IMRT, PBT resulted in significantly lower mean heart dose (MHD) and heart V5, V10, V20, V30, and V40 as well as lower radiation exposure to the four chambers and four coronary arteries. Compared with PSPT, IMPT resulted in significantly lower heart V20, V30, and V40 but not MHD or heart V5 or V10. IMPT also resulted in significantly lower radiation doses to the left atrium, right atrium, left main coronary artery, and left circumflex artery, but not the left ventricle, right ventricle, left anterior descending artery, or right coronary artery. Factors associated with lower MHD included PBT ( P < 0.001), smaller planning target volume (PTV; P < 0.001), and gastroesophageal junction (GEJ) tumor ( P < 0.001). Among PBT patients, factors associated with lower MHD included IMPT ( P = 0.038), beam arrangement other than AP/PA ( P < 0.001), smaller PTV ( P < 0.001), and GEJ tumor ( P < 0.001). Conclusions: In patients with mid- to distal esophageal cancer, PBT results in significantly lower radiation exposure to the whole heart and cardiac substructures than IMRT. Long-term studies are necessary to determine how this cardiac sparing effect impacts the development of coronary artery disease and other cardiac complications.